PERANAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MEMEDIASI PENGARUH KEPUASAN PEGAWAI DAN PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN HOTEL BINTANG LIMA DI JAKARTA PUSAT - Dewani Hapsari (Jurnal Manajemen dan Pemasaran Jasa, 2010)
The purpose of this research is to propose a model which organizational citizenship behavior and jobperformance mediate the influence of job satifaction and human resources management practicestoward service quality at Grand Sahid Jaya Jakarta.The conceptual framework consists of the following constructs : job satisfaction, human resourcesmanagement practices, organizational citizenship behavior, job performance, and service quality.Moreover, four hypotheses were developed and tested. Instrument test of validity and reliabilitywere used to test the validity of the measures, while multiple regression from Statistical Package forSocial Science (SPSS) was used in hypotheses testing. Data were collected from Grand Sahid Jayaemployee, Jakarta.The objectives of this research is to analyze the job satisfaction influence organizational citizenshipbehavior at Grand Sahid Jaya Jakarta, analyze the human resources practices toward organizationalcitizenship behavior, analyze the organizational citizenship behavior influence job performance andanalyze job performance influence service quality at Grand Sahid Jaya JakartaThe result indicate that all hypothesis was supported, indicated that job satisfaction have significantinfluence toward organizational citizenship behavior, human resources practices have significantinfluence toward organizational citizenship behavior, organizational citizenship behavior havesignificant influence toward job performance and job performance have significant influence towardservice qualityKeywords : Service quality, organizational citizenship behavior, job performance, job satisfaction,human resources management practices,